(untitled) (Historia, 2021)
Racial integration on trains and railway stations excited anxiety for the first time in Natal in the 1880s and in the Cape in the next decade. In both colonies there were white passengers who complained about sharing facilities with dirty, uncivilized and sickly blacks. Some blacks complained about discrimination. Train officials were ordered to separate whites and blacks whenever possible. In both colonies parliament approved motions for more effective racial segregation on trains. Passengers were therefore to a certain extent accustomed to segregation when stricter measures, of Transvaal origin, were applied after Union in 1910. Rassevermenging op treine en spoorwegstasies het vir die eerste keer openbare ongerust-heid in Natal in die 1880s en in die Kaap in die volgende dekade opgewek. In albei kolonies was daar blanke passasiers wat gekla het dat hulle fasiliteite met vuil, onbeskaafde en sieklike swartes moet deel. Sommige swartes het oor diskriminasie gekla. Treinbeamptes is aangesê om blankes en swartes wanneer moontlik van mekaar te skei. In albei kolonies het die parlement mosies vir meer doeltreffende rasseskeiding op treine goedgekeur. Passasiers was dus in ’n mate gewoond aan segregasie toe strenger maatreels afkomstig van die Transvaal na Uniewording in 1910 toegepas is.